Impacto en la implementación del software StiloStock para el manejo de los inventarios dentro de la empresa GERARDO STYLE (2023)
Barberia GERARDO Style" is an aesthetic center in Santa Marta, Colombia, specialized in men's services such as haircuts and beard care. Although it has gained recognition in its community, it faces an inventory control problem. The research focuses on implementing an inventory control system to address this challenge, justifying the social, economic and environmental importance. The study seeks to analyze the company's current process and apply an inventory system (StiloStock) and examine the benefits. Theoretical topics such as cash flow, inventory management, ABC classification, demand and trend analysis, economies of scale and personnel training are addressed. Additionally, the implementation of the inventory system is expected to generate employment, improve efficiency and promote environmentally responsible practices, contributing to local economic growth.